2006
DOI: 10.1002/chem.200501404
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Hydrothermal Synthesis and Growth Mechanism of Various Nanostructured Films of Copper and Silver Tellurides

Abstract: Various nanostructured films of copper and silver tellurides were hydrothermally grown on the corresponding metal substrates through reactions between metal foils and tellurium powder in different media. Interesting morphologies including nanowires, nanorods, nanobelts, nanosheets, and hierarchical dendrites were obtained. The nanostructured films were characterized by using X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and high-resolution TEM (HRTEM). A g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…3C and D) revealed that the crystal structure of both transformation products could be indexed to monoclinic (b) Ag 2 Te with characteristic (200), (À211), (À210), (À113), and (À303). [50,51] EDX results ( Fig. 3E and F) show that Ag 2 Te NPs which are a product of original CdTe NPs in ion replacement reactions have a much high percentage of sulfur in comparison with Ag 2 Te NWs from the stabilizerdepleted CdTe NPs solution (24.8% vs. 8.2%, Tables 1 and 2).…”
Section: Optical and Structural Characterizationmentioning
confidence: 98%
“…3C and D) revealed that the crystal structure of both transformation products could be indexed to monoclinic (b) Ag 2 Te with characteristic (200), (À211), (À210), (À113), and (À303). [50,51] EDX results ( Fig. 3E and F) show that Ag 2 Te NPs which are a product of original CdTe NPs in ion replacement reactions have a much high percentage of sulfur in comparison with Ag 2 Te NWs from the stabilizerdepleted CdTe NPs solution (24.8% vs. 8.2%, Tables 1 and 2).…”
Section: Optical and Structural Characterizationmentioning
confidence: 98%
“…Nanoparticle preparation has been developed through various methods including ultraviolet irradiation photo reduction (Zhou et al 1999), sonoelectrochemical synthesis of nanoparticles (Saez and Mason 2009), microwave-assisted synthesis (Mallikarjuna and Varma 2007), electrocrystallization (Murashova et al 2003), electroless metal deposition (Qiu et al 2005), photo reduction (Yonezawa et al 2005), laser ablation (Brito-Silva et al 2010;Tsuji et al 2008;Jiménez et al 2007). In addition, several chemical and biological procedures have been offered involving: polyol (Sun et al 2003;Zhu and Hu 2004;Gautam et al 2007;Wiley et al 2005), hydrothermal (Zhang et al 2006), template (Adhyapak et al 2004;Sun et al 2005;Hong et al 2001), surfactant self-assembly (Pileni 2003) as chemical methods. Culture supernatant of bacteria with microwave irradiation (Saifoddin et al 2009), and production of metal nanoparticles by microbes (Kannan Badri and Natarajan 2010) are some examples of biological synthesis of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous reaction environment has proved to be sometimes ideal to obtain high-quality nanocrystals [4][5][6]. For example, Zhang et al [7] developed a general solution phase strategy to grow nanostructured metal chalcogenides through hydrothermal reaction of metal foils with chalcogen powders. Li et al [8] reported the synthesis of ME (M ¼ Cu, Sn, Co 2+ , Ni 2+ , Mn 2+ , or Pb 2+ ; E ¼ S or Se), Ag 2 E, M 2 E 3 (M ¼ Bi or Sb) NCs through reaction of sulfur and selenium with elemental or ionic metals with ethylenediamine as strong coordinating agent.…”
Section: Introductionmentioning
confidence: 99%